Republic of Estonia : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Estonia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Republic of Estonia's 2007 Article IV Consultation reports that surging domestic demand has widened the external current account deficit and pushed the economy against capacity constraints. Wage increases have begun to erode competitiveness and kept inflation above the Maastricht threshold for euro adoption. There are signs of an incipient slowdown, but a resurgence of demand and an eventual hard landing, with growth stagnating, cannot be ruled out. A strong fiscal stance is needed to subdue wage and income expectations and improve the odds of a soft landing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet